The Australian and New Zealand Fontan Registry Quality of Life Study: Protocol for a population-based assessment of quality of life among people with a Fontan circulation, their parents, and siblings - Daniel S J Costa; Kim Dalziel; Yves d’Udekem; David S Winlaw; David S Celermajer; Nadine A Kasparian; Diana Zannino; Rachel Bishop; Kate H Marshall; Susan R Woolfenden; Gary F Sholler (BMJ Open)
Introduction Advances in the care of patients with single-ventricle congenital heart disease have led to a new generation of individuals living with a Fontan circulation. For people with Fontan physiology, physical, psychological and neurodevelopmental challenges are common. The objective of this study is to describe and develop a deeper understanding of the factors that contribute to quality of life (QOL) among children, adolescents and adults living with a Fontan circulation across Australia and New Zealand, their parents and siblings.Methods and Analysis This article presents the protocol for the Australian and New Zealand Fontan Registry (ANZFR) QOL Study, a cross-sectional, population-based study designed to examine QOL among people of all ages with a Fontan circulation, their parents and siblings. Study eligibility criteria includes (1) individuals with a Fontan circulation aged ≥6 years, at least 12 months post-Fontan procedure and enrolled in the ANZFR; (2) parents of individuals enrolled in the ANZFR; and (3) siblings aged ≥6 years of an individual enrolled in the ANZFR. A novel, online research platform is used to distribute personalised assessments tailored to participant age and developmental stage. A suite of validated psychometric self-report and parent-proxy report instruments capture potential correlates and predictors of QOL, including symptoms of psychological distress, personality attributes, coping and cognitive appraisals, family functioning, healthcare experiences and costs, access to emotional support and socioeconomic factors. Clinical characteristics are captured via self-report and parent-proxy report, as well as the ANZFR. Descriptive analyses and multilevel models will be used to examine QOL across groups and to investigate potential explanatory variables.Ethics and Dissemination Approval has been obtained from all relevant Human Research Ethics Committees (HRECs), including the Sydney Children’s Hospitals Network and the Royal Children’s Hospital Melbourne HRECs. Study findings will be published in peer-reviewed journals and presented at national and international meetings and seminars.